Spectral Characteristics of Sports and Occupational Tinted Lenses - Chou, B.R.; Cullen, A.P. (Canadian Journal of Optometry, 2021)
Tinted spectacle lenses are used for a variety of reasons including comfort, reduction of glare, enhanced vision under certain conditions, cosmesis, status for the wearer, and protection from radiation and/or impact. The selection of tints for protection from hazardous levels of optical radiation in industry and other work environments is well documented and governed by various standards. However, the selection of tinted lenses for other uses is usually arbitrary and made without professional advice. The purchaser often chooses tinted lenses on the basis of advertising material provided by the manufacturer. Few manufacturers provide accurate lens transmittance data, and some make claims which cannot be substantiated. We have previously reported on tinted prescription spectacle lenses and contact lens materials. However, the majority of tinted lenses worn for sports and occupational purposes do not fall into these categories. Thus, the object of this study was to evaluate the absorptive characteristics of a variety of special-purpose non-prescription tinted lenses.